Surface Fractal Study of Perovskite Alumina Ceramic Membrane Prepared By Sol-Gel Method From Adsorption Isotherm Description - Ahmad, A. L.; Abd Shukor, S. R.; Idrus, N. F.; Othman, M. R. (2005)
Perovskite alumina membrane has been synthesized by the sol-gel method. The molar ratio of alkoxide to water and acid 1:100:0.07 was used to prepare the sol. Observation were made on pore size and BET surface area at different temperature using N2 sorption analysis. The average pore size increased with increasing of temperature. Pore surface roughness changes in perovskite-alumina mebrane have been investigated by surface fractal dimension analysis. The Frenkel-Halsey-Hill (FHH) model for multilayer adsorption was applied to obtain the surface fractal dimension. Surface fractal dimension increases while calcined from 400C to 600C but decreases at temperature 800C. SEM analysis observed the surface morphology of the mebrane.